Evaluation of response and energy in actively controlled structures. - Wong, Kevin K.F.
A computational method of energy evaluation is derived to study the elastic responses and energy distribution of actively controlled single degree of freedom (SDOF) structures during earthquakes. Contrary to the common perception that applying active control force pumps energy into the structure, the applied control force can actually reduce the energy in the structure by reducing the input energy from earthquakes to the structure. In addition, applying control force can dissipate a large amount of energy in the structure when this control force is applied in the direction opposite to the displacement and velocity responses. To demonstrate this energy mechanism in active controlled structures, the two most popular control algorithms, optimal linear control (OLC) and instantaneous optimal control (IOC) algorithms, are used to calculate the control response and energy spectra. One step time delay is incorporated into the algorithms to take into consideration the practical aspect of active control. The effects of different earthquakes and damping ratios on control energy and response spectra are studied. These studies show that both OLC and IOC are very effective in reducing the structural displacement and velocity responses by reducing the input earthquake energy as well as dissipating a large amount of energy in the structure.
Keywords: Optimal linear control; Instantaneous optimal control; Input energy; Strain energy; Kinetic energy; Control energy